Range extensions of endemic butterflies in Western Mindanao, Philippines - Abijay, Leizel Mae R.; Badon, Jade Aster T.; Nuñeza, Olga M.; Maceda, Justin N.; Mondejar, Eddie P. (2023)
A recent assessment on the butterflies of Mount Gutom, Zamboanga del Norte, Mindanao, Philippines, resulted in range extensions of Mindanao endemic nymphalid butterflies such as Zethera hestioides and Zethera musa
Keywords: Butterflies; Endemic animals; Mountains -- Mindanao